3D Microsupercapacitors: 3D Interdigitated Microsupercapacitors with Record Areal Cell Capacitance (Small 27/2019). Issue 27 (5th July 2019) - Ferris, Anaïs; Bourrier, David; Garbarino, Sébastien; Guay, Daniel; Pech, David
Abstract : Microscale energy storage for embedded electronics remains a major challenge at the dawn of the Internet of Things. In article number 1901224, David Pech, Daniel Guay, and co‐workers describe the integration of 3D pseudocapacitive electrodes on a silicon wafer to realize all‐solid‐state interdigitated microsupercapacitors with a record cell capacitance of 812 mF cm −2 per footprint area.